Współkonstruowanie znaczenia w dyskursie metajęzykowym na lekcji języka obcego - Szymankiewicz, Krystyna (Neofilolog, 2019)
Metalinguistic discourse is the most common type of foreign language class-room discourse. It is commonly used by teachers in order to give explana-tions on language use, forms and meanings. While teachers dominate in this kind of discourse, students seem to remain passive. How can we promote students’ communicative and cognitive activity? This article focuses on teach-ers’ and learners’ strategies for negotiation of meaning in the case of written input. An analysis of four lessons of French as a foreign language recorded in a secondary bilingual school in Warsaw was carried out in order to reveal the metalinguistic strategies that enhance the discursive co-operation between the participants and, in this way, co-construction of meaning.